Kajian Efisiensi Usaha Budidaya Ikan Kuwe (Caranx.Sp) Dalam Keramba Jaring Apung Di Desa Lolibu Kecamatan Lakudo Kabupaten Buton Tengah - Saharuddin; Riani, Irdam; Nurdiana A; Budiyanto; Wa Ode, Piliana; Sidiq, Azwar (Jurnal Sosial Ekonomi Perikanan, 2023)
This study aims to determine the efficiency of the Kuwe fish cultivation business in Floating Net Cages (KJA) in Lolibu Village, Lakudo District, Central Buton Regency. This research was carried out in June 2021. The data were taken by 7 KJA business actors. The measured variable costs include the amount of wages, feed, fuel, oil, and seeds while the fixed costs include cages, nets, engines, boats and drums used in the Kuwe fish farming business in KJA. The data obtained are efficiency analysis. The results showed that the R/C and HPP values ​​in the Kuwe Fish business in floating net cages in Lolibu Village, Lakudo District, Buton Regency, it can be concluded that the business has been efficient. Cultivators with higher stocking densities with higher production will be more efficient